PERFORMANCES OF CREATIVE HUBS IN INDONESIA: LESSONS FROM SEMARANG’S EXPERIENCE - Tyas, Wido Prananing; Surahman, Idha Apriliani (Jurnal Pengembangan Kota, 2024)
This study evaluates the performance of Creative Hub Semarang (CHS) in fulfilling its dual objectives as a collaborative space for creative economy actors and a tourism destination. Utilizing a mixed-methods approach, the research combines quantitative surveys with visitors to capture perceptions and satisfaction and qualitative in-depth interviews with government and creative actors. Results reveal that CHS’s strategic location in Kota Lama presents an opportunity to bridge the creative economy with tourism. About its role as a creative hub, while CHS has provided essential infrastructure and networking opportunities, its operational model and fragmented management hinder its ability to foster active collaboration and innovation. Challenges include limited trust between government entities and creative actors, bureaucratic constraints, and restrictive regulations. To strengthen CHS’s role, a more integrated and collaborative management approach is needed, alongside clearer communication of its objectives.